The Influence of Globalization on the Harmonization of International and National Law - Junaidi Lubis; Melky Suhery Simamora; Bambang Sutejo; Dedek syafrizal (Outline Publisher, 2024)
Globalization has had a significant impact on the harmonization of international and national laws, affecting areas such as trade, environment, and human rights. This study explores the impact of globalization on legal harmonization, identifying key drivers such as economic integration, technological advancement, and the role of international organizations. It also highlights emerging challenges, including legal pluralism, cultural resistance, and disparities in institutional capacity across countries. Using a qualitative approach, legal analysis is conducted to identify patterns of convergence and divergence across legal systems, including common law, civil law, and hybrid legal systems. Case studies such as the implementation of the Paris Agreement, the adaptation of WTO trade law standards, and the mainstreaming of human rights in developing countries reveal the success rates and obstacles in harmonization. The results show that while harmonization promotes global cooperation and reduces legal protection, challenges remain. Fragmentation of international law, geopolitical tensions, and differences in local values ​​are key barriers. To address these, the study recommends an adaptive framework, enhanced multilateral cooperation, and investment in developing country capacity building. In conclusion, legal harmonization requires a balance between global norms and local relevance, so as to create an inclusive and effective legal system. A collaborative approach involving stakeholders across borders is key to bridging the gap between international standards and national realities.